Groundwater Potential of the East and North Sides of Gunungmasigit Village: A Case Study - Wijaya, Dwi Suyandi Pasa; Iskandarsyah, Teuku Yan W. M.; Yoseph, Boy (Newinera Publisher, 2024)
The purpose of this research is to conduct a groundwater survei by analyzing the availability of groundwater on the east and north sides of Gunungmasigit Village, Kec. cipatat, kab. west bandung (case study: PPSDM Geominerba field campus KESDM). The aim of this study was to determine the potential for groundwater in the northern area of the PPSDM Geominerba Field Campus and to find information regarding the absence of groundwater after drilling was carried out in 2019 in the area on the east side of the PPSDM Geominerba Field Campus. The research administrative area is located in Gunungmasigit Village, Kec. Cipatat, Kab. West Bandung (PPSDM Geominerba field campus KESDM). The author will focus more on the end of Cipatat-1 (north side) on the map, where it is located in the gate area of the Geominerba PPSDM Field Campus. This study uses the geoelectrical measurement method. One of the geoelectrical methods is the resistivity or resistivity method. This method studies the subsurface structure based on the different resistivity values in the rock with depth. Data analysis used IPI2WIN Software with track 1 having a length of 200 meters and track 3 having a length of 400 meters. In the results of Cipatat-1 it is suspected that there is a water-carrying layer at a depth of 11.9 – 45.9 m. Meanwhile, the results of Cipatat-3 suggest that there is a water-carrying layer at a depth of 26.3 m.